Narratives and numbers : empirical studies of Pentecostal and Charismatic Christianity - Cartledge, Mark J., 1962- (Global Pentecostal and Charismatic Studies, 2017)
In Narratives and Numbers: Empirical Studies of Pentecostal and Charismatic Christianity Mark J. Cartledge provides a rich set of essays on key themes in Pentecostal and Charismatic Christianity. Using empirical research methods drawn from the social sciences he interrogates his originally gathered data by means of theology and sociology. These studies address such issues as glossolalia, prophecy, spirituality, gender and the family, the doctrine of the Trinity, socialization, altruism and the practice of healing. Collectively they provide original insight into one of the most vibrant forms of Christianity today. Additionally, these studies model how empirical research in religion can be bought into conversation with theological discourse. The findings of this research can be used by scholars and students from different perspectives and disciplinary contexts.